A New Projection From the Deep Cerebellar Nuclei to the Hippocampus via the Ventrolateral and Laterodorsal Thalamus in Mice - Bohne, Pauline; Schwarz, Martin K.; Herlitze, Stefan; Mark, Melanie D. (Frontiers in Neural Circuits, 2019)
The cerebellar involvement in cognitive functions such as attention, language, working memory, emotion, goal-directed behavior and spatial navigation is constantly growing. However, an exact connectivity map between the hippocampus and cerebellum in mice is still unknown. Here, we conducted a tracing study to identify the sequence of transsynaptic, cerebellar-hippocampal connections in the mouse brain using combinations of recombinant adeno-associated (rAAV) and pseudotyped deletion-mutant rabies (RABV) viruses. Stereotaxic injection of a primarily anterograde rAAV-WGA (wheat germ agglutinin)-Cre tracer virus in the deep cerebellar nuclei (DCN) of a Cre-dependent tdTomato reporter mouse resulted in strong tdTomato labeling in hippocampal CA1 neurons, retrosplenial cortex (RSC), rhinal cortex (RC) as well as thalamic and cerebellar areas. Whereas hippocampal injections with the retrograde tracer virus rAAV-TTC (tetanus toxin C fragment)-eGFP, displayed eGFP positive cells in the rhinal cortex and subiculum. To determine the sequence of mono-transsynaptic connections between the cerebellum and hippocampus, we used the retrograde tracer RABVΔG-eGFP(EnvA). The tracing revealed a direct connection from the dentate gyrus in the hippocampus to the retrosplenial cortex (RSC), RC and subiculum (S), which are monosynaptically connected to thalamic laterodorsal and ventrolateral areas. These thalamic nuclei are directly connected to cerebellar fastigial (FN), interposed (IntP) and lateral (Lat) nuclei, discovering a new projection route from the fastigial to the laterodorsal thalamic nucleus in the mouse brain. Collectively, our findings suggest a new cerebellar-hippocampal connection via the laterodorsal and ventrolateral thalamus to RSC, RC and S. These results strengthen the notion of the cerebellum’s involvement in cognitive functions such as spatial navigation via a polysynaptic circuitry.